Spillover of Financial Innovations during Covid-19: A Cross-Country Analysis - Rout, Sanjay Kumar (Asian Development Policy Review, 2020)
The main objective of this work is to investigate the magnitude of cross-country financial innovations spillover and its direction among top ten economies (in terms of gross domestic product) such as US, China, Japan, Germany, India, UK, France, Brazil, Canada, and Russia, during Covid-19 pandemic (from 1st January to 10th July 2020). Employing Diebold and Yilmaz’s VAR based spillover approach; the empirical results demonstrate that the financial innovations spillover is very high during Covid-19 pandemic. Specifically, the total financial sector innovations spillover for full sample is 49.20%, on average, when estimation based on only 3-months government bond yield price whereas total spillover is 62% on average when spillover is measured through composite financial sector index. The marginal variation in empirical results between two models due to the following reasons; (i) latter model is based on composite indices that capture a wider picture of cross-country spillover, and (ii) spillover is higher with long terms bond yield which incorporated in latter model. The empirical results imply more than one-half of the total variance of forecast errors is explained by innovations spillover across countries. Nevertheless, it will provide better guidance to investors, portfolio managers, and policymakers during this current economic disaster to make right decision. The result is found to be robust.